2012
DOI: 10.1371/journal.pone.0037740
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of the Protozoan Parasite Entamoeba invadens Revealed Activation of Unpredicted Pathway during Encystation

Abstract: Encystation, which is cellular differentiation from the motile, proliferative, labile trophozoite form to the dormant, resistant cyst form, is a crucial process found in parasitic and free-living protozoa such as Entamoeba, Giardia, Acanthamoeba, and Balamuthia. Since encystation is an essential process to deal with the adverse external environmental changes during the life cycle, and often integral to the transmission of the diseases, biochemical understanding of the process potentially provides useful measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 71 publications
7
64
0
Order By: Relevance
“…This finding is consistent with recent work [56] in which the metabolome of encysting E. invadens was determined. In this study it was observed that during encystation and in mature cysts (48 h and 120 h post-encystation), basic metabolic processes such as glycolysis were drastically decreased, and glucose metabolism redirected to cyst wall synthesis.…”
Section: Resultssupporting
confidence: 93%
“…This finding is consistent with recent work [56] in which the metabolome of encysting E. invadens was determined. In this study it was observed that during encystation and in mature cysts (48 h and 120 h post-encystation), basic metabolic processes such as glycolysis were drastically decreased, and glucose metabolism redirected to cyst wall synthesis.…”
Section: Resultssupporting
confidence: 93%
“…However, despite its dormant nature, genes encoding several metabolic enzymes involved in nucleotide metabolism, energy, lipids, and sphingolipids metabolism were still transcribed during the late phase of encystation (Tables S6 and S7). In our previous study we discussed detailed analysis of metabolisms of glycolysis, amino acid, cyst wall biosynthesis [46]. Briefly, among genes involved in chitin biosynthesis, the transcript level of a gene encoding for glucosamine-fructose-6-phosphate aminotransferase (GFAT, EIN_136750), which is the first and rate limiting enzyme of the chitin biosynthetic pathway, was increased at 24 h of encystation (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Trophozoites of the E. invadens IP-1 strain were cultivated axenically as described previously in BI-S-33 medium at 26°C (17,29). To induce encystation, 1-wk-old trophozoite cultures were harvested and transferred to encystation medium at a final concentration of 6 × 10 5 /mL as described (17,29), with slight modifications. Cells were sampled at the indicated times after exposure to the encystation medium.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were sampled at the indicated times after exposure to the encystation medium. The number and the percentage of cysts formed were determined as described previously (29). CS was dissolved in DMSO at 50 mM, and chlorate was dissolved in BI-S-33 or encystation medium at 500 mM, as stock solutions.…”
Section: Methodsmentioning
confidence: 99%